Smart prepaid traffic fines system using RFID, IoT and mobile app - Salam A. W. Al-abassi; Karrar Y. A. Al-bayati; Mohammad R. R. Sharba; Layth Abogneem (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This work is intended to deliver an intelligent traffic system using radio frequency identification (RFID) technology. It designed and implemented in a way where fines are autonomously registered. In addition, a mobile app was built to assist traffic officers managing their field works. Low cost equipment’s have been used such as RFID technology, passive tags, processing unit (personal computer), and a connection system. First stage is represented by collecting data using the RFID, where it reads any identified tag that attached with vehicles. Next, a certain data are transmitted to the server using internet network communication system. The server is responsible for processing these data according to a pre-defined rules. Finally, police officers can use the mobile app to perform several tasks according the processed data such as monitoring a specific car, register a new car ID and others.